2025 Global report on food crises - Food Security Information Network; Global Network Against Food Crises (Food Security Information Network and Global Network Against Food Crises, 2025)
The Global Report on Food Crises (GRFC) 2025 provides consensus-based analysis on acute food insecurity, acute malnutrition and population displacement in countries/territories identified as having food crises in 2024 . It is produced in collaboration with technical agencies and partners to provide a consensual analysis based on rigorous methodologies and the consolidation of data from various sources.